Corporate Governance and Bank Performance: Evidence from Chinese Listed Banks - Fu, Yu (2022)
Using a sample of 30 Chinese listed banks over the period 2014 to 2020, this paper aims to investigate the impact of corporate governance on bank performance. Panel data were used to analyse how board structure (board size, board independence, board gender diversity), ownership structure (foreign ownership, state-owned ownership) and risk governance (the presence of risk committees and chief risk officers, risk committee independence and risk committee size) affect banks’ financial performance (return on assets, return on equity, net interest margin and earnings per share). The main findings suggest that board structure, ownership structure and risk governance affect the performance of Chinese banks to a certain extent. Specifically, board size and the percentage of independent directors are positively related to bank performance, while the percentage of female directors is negatively related to bank performance; both foreign ownership and state-owned ownership have a positive impact on bank performance, and foreign ownership affects performance to a greater extent; the establishment of risk committees increase bank profitability, but the chief risk officer and the proportion of independent directors on risk committees decline bank profitability, and the size of the risk committee is irrelevant to the bank performance. Summing up, the Chinese government should continue to promote a better role for these governance mechanisms in bank governance, focusing on the optimising the risk governance system.